Large Deformation Analysis of Trenched Pipelines Under Lateral Displacements - Kianian, Morteza; Shiri, Hodjat (Geotechnical and geological engineering, 2023)
Subsea pipelines are commonly trenched and backfilled for stability and protection in shallow waters. Using trench excavation spoils for backfilling is a cost-effective solution that is widely used in practice. This kind of backfilling material is highly remoulded during the construction process and exposed to environmental loads. The buried pipelines may undergo large lateral displacement because of ground movement, ice-gouging, etc. The experimental studies have shown that the different stiffness between the backfill and native ground along with pipeline-backfill-trench configuration may significantly affect the interactive soil deformation and failure mechanisms around the pipe and consequently the lateral soil resistance. However, the trenching and backfilling effects are currently neglected by the existing design codes. In this paper, the pipeline-backfill-trench interaction was comprehensively investigated using Coupled Eulerian–Lagrangian (CEL) analysis and verified against the centrifuge experiments. The study revealed the significance of several important parameters and their effect on the lateral response of the buried pipelines including pipeline-trenchbed interaction, strain softening, pipe surface roughness, and backfill shear strength.